Efeitos do ozônio no clareamento dental caseiro: um estudo clínico, randomizado, duplo-cego - Campolina, Murilo Guimarães (2024)
This study evaluated the impact of ozonized sunflower oil application during at-home tooth bleaching on tooth sensitivity (TS), color change, and patient perception. A double-blind, randomized clinical trial was conducted with 40 participants, divided into experimental (ozonized sunflower oil) and placebo (sunflower oil) groups. The oil was applied in trays for 1 minute following each application of 10% hydrogen peroxide gel for 30 minutes, over a total of 21 sessions. TS was assessed daily using a visual analog scale (VAS) and a numerical rating scale (NRS). Tooth color was measured with a spectrophotometer (ΔEab, ΔE00, ΔWID) and a visual shade guide (ΔSGUs) at baseline, 1 week (T1), and 1 month (T2) post-treatment. Patient perception was evaluated using Likert scale-based forms. Results showed that 72.5% of patients reported TS during bleaching, regardless of the group. No significant differences were found in TS intensity between the groups (p=0.536) or in the number of painful days (p=0.256). Color change was similar between the groups (p>0.05); however, ΔEab and ΔE00 at T2 were lower than at T1 (p=0.010 and p=0.026, respectively). Patient perception regarding taste (p=0.002) and odor (p=0.010) differed significantly, with ozonized sunflower oil being considered unpleasant for use. It was concluded that the application of ozonized sunflower oil during at-home tooth bleaching did not reduce TS or affect color change compared to the placebo. Patient perception was negative primarily due to the unpleasant taste and odor of ozonized sunflower oil. Thus, despite various mechanisms of action, ozonized sunflower oil did not mitigate tooth sensitivity or influence color change during at-home tooth bleaching, with its taste and odor negatively impacting patient comfort.